Dependence of the nascent vibrational distribution of NO(v) on the photolysis wavelength of NO2 in the range lambda = 266-327 nm measured by time-resolved Fourier transform infrared emission. - Brooks, C; Hancock, G; Saunders, M (2007)
Time-resolved FTIR has been used to study the photodissociation of NO2 at photolysis wavelengths of lambda = 266, 282, 295, 308, 320 and 327 nm. Nascent vibrational distributions of the NO(v) fragment have been determined at all wavelengths: 266 nm photolysis populates NO(v = 1-7) and shows a distribution that is inverted at v = 5, whereas 327 nm photolysis populates NO(v = 1-3) and is inverted at v = 2. Surprisal plots were performed on the nascent distributions presented in this work and on all data sets available in the literature in the range 266-370 nm in order to parameterise the wavelength dependence of the nascent distribution of NO(v) from NO2 photolysis. In general, the surprisal parameter was found to be a linear function of wavelength and was used to generate a simple model for the wavelength dependence of the nascent distribution of NO(v) in the region lambda = 265-372.5 nm. The results give a more accurate parameterisation of the formation of NO(v) of use in atmospheric modelling.